De plantadores de farinha a colhedores de água: uma leitura epistemológica do Sistema Tradicional da Agricultura Camponesa no Maranhão - Damasceno Junior, Jackson Bouéres (2021)
It is proposed to discuss some intrinsic aspects of the flour production process modulated by social and productive organization technologies, with emphasis on the environmental services originated during these activities. Environmental services are greater than those consumed and attribute to these peoples an important role in the process of sustainability in a fragile ecosystem. This research has a qualitative and quantitative approach, and includes ethnographic incursions made by researchers. The analyzes indicate the importance of recognition by the State through structuring public policies and not social transformation actions, which do not validate traditional production systems.